Analysis of Internal Control System of Cash Receipts and Expenditures at The Cv. Lestari Bumi Khatulistiwa - B41112160, Horas Jusuf Mahardhika Marpaung (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT In the cash receipts and disbursements, needed a good procedure in accordance with management policies that have been set. Cash receipts and payments made, outside of the established procedures, will allow to fraud, theft and embezzlement of cash. With the implementation of good procedures, will minimize all forms of fraud, theft and embezzlement of cash that may be made by parties who have the opportunity and access to the company's cash. The object of this study is the CV. Lestari Bumi Khatulistiwa, a company located in the city of Pontianak engaged in mapping. The purpose of this study was to determine the effectiveness of the system of internal control over cash receipts and expenditures on a CV. Lestari Bumi Khatulistiwa. This study is a qualitative research and data collection techniques used is through observation, interviews and documentation. While analysis tools used in this research is the organizational structure, flowcharts, internal control questionnaires, and related documents. Results of research conducted concluded that CV. Lestari Bumi Khatulistiwa already implementing a good system in its cash receipts and disbursements. However, there is an excessive delegation of authority to the department which deals with financial companies. Delegation of authority to this excessive, can lead to fraud, theft and embezzlement of cash held companies. Keywords: Internal Control System, Cash Receipts, Cash Expenditures.